If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 66 + -8a = 2(19 + -3a) 66 + -8a = (19 * 2 + -3a * 2) 66 + -8a = (38 + -6a) Solving 66 + -8a = 38 + -6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6a' to each side of the equation. 66 + -8a + 6a = 38 + -6a + 6a Combine like terms: -8a + 6a = -2a 66 + -2a = 38 + -6a + 6a Combine like terms: -6a + 6a = 0 66 + -2a = 38 + 0 66 + -2a = 38 Add '-66' to each side of the equation. 66 + -66 + -2a = 38 + -66 Combine like terms: 66 + -66 = 0 0 + -2a = 38 + -66 -2a = 38 + -66 Combine like terms: 38 + -66 = -28 -2a = -28 Divide each side by '-2'. a = 14 Simplifying a = 14
| (x^2-x)-14(x^2-x)+24=0 | | 2x+7=6x+31 | | y+8=0.5(x-3) | | 3w-12=-27 | | 2a^2=1+a | | (25x^2-100x+50)+(50x-50)(2x)-(20x)(5-5x)-50x^2=0 | | x-8=-3x+11 | | d(t)=(20+3t)t | | 2(2x+8)+4=4x+20 | | Y-1(12-2x)=6 | | 2x^2+7x-32=0 | | X+15=3x-75 | | 65-2c=-23 | | (30-1y)+1y=30 | | -140/21 | | -6x+10y=134 | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(-10x^2)=0 | | 180+7x=360 | | (20-2x)(10-2x)(x)= | | (25x^2-100x+50)(50x-50)(2x)-(20x)(-5)(5-5x)(10x^2)=0 | | 5c+3=29 | | 2x+2(x+6)=12 | | 3x^2-12x^2+36x=0 | | 4s-8=15 | | 2x^2-36x=720 | | 18+8x=88 | | (25x^2-100x+50)(50x-50)(2x)-(-100x)(5-5x)(10x^2)=0 | | 5/7x3/5 | | 5y-20+110+y=180 | | W-4.40=9.60 | | x=30+-1y | | (9y+3)(3x+10)= |